MEMBANGUN PENDIDIKAN DASAR MELALUI PERSPEKTIF ANTROPOLOGI DAN KEBUDAYAAN - Nurjasriati; Neviyarni S; Zelhendri Zen (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Primary education plays a strategic role in shaping children's character, cultural identity, and social skills. However, globalization and an overly cognitive-oriented educational approach have marginalized local cultural values. This study aims to analyze the application of anthropological perspectives in developing culture-based primary education. The research method employed is a literature review, examining various scientific articles, textbooks, and relevant studies published within the last 5–10 years. The findings reveal that integrating local culture into primary education strengthens students' sense of identity, increases learning motivation, and fosters adaptive and inclusive personalities. Culture-based education also plays a crucial role in transmitting core values from one generation to the next. Nevertheless, the implementation of culture-based education in Indonesia still faces challenges, including limited teacher training and a lack of culturally representative learning resources. To overcome these obstacles, it is essential to develop a curriculum based on local wisdom, provide continuous teacher training, and supply culturally sensitive teaching materials. Applying an anthropological perspective to primary education is a key strategy for nurturing a young generation with strong character and deep-rooted cultural identity.